Makna dan Nilai Leksikon Menjahit Kemeja di Kecamatan Comal: Kajian Antropolinguistik - Sari, Erna Puspita; Widodo, Widodo (Faculty of Languages and Arts, Universitas Negeri Padang, 2025)
This study examines the lexicon used in shirt sewing activities in Comal District from an anthropological perspective. The study aims to reveal the lexical meaning, cultural meaning, and philosophical values contained in the sewing terminology. Using a qualitative descriptive approach, data were collected through participant observation, in-depth interviews, and documentation, then validated using source triangulation. The results of the study identified 36 distinctive lexicon classified into the categories of tools (15), materials (3), techniques (11), and shirt parts (7). Analysis shows that in addition to their referential function, 11 lexicon terms contain deep cultural meanings, and 21 lexicon terms reflect the richness of language and social identity based on the economic strata of the local community. This study concludes that sewing lexicon is not merely a technical communication tool, but a crucial instrument of social cohesion. This documentation contributes to the preservation of Javanese cultural linguistics for the Alpha generation amid the tide of modernization.